Implementation and Operational Research: Evaluation of a Public-Sector, Provider-Initiated Cryptococcal Antigen Screening and Treatment Program, Western Cape, South Africa. (1st June 2016) - Vallabhaneni, Snigdha; Longley, Nicky; Smith, Mariette; Smith, Rachel; Osler, Meg; Kelly, Nicola; Cross, Anna; Boulle, Andrew; Meintjes, Graeme; Govender, Nelesh P.
Abstract : Background: Screening for serum cryptococcal antigen (CrAg) may identify those at risk for disseminated cryptococcal disease (DCD), and preemptive fluconazole treatment may prevent progression to DCD. In August 2012, the Western Cape Province (WC), South Africa, adopted provider-initiated CrAg screening. We evaluated the implementation and effectiveness of this large-scale public-sector program during its first year, September 1, 2012–August 31, 2013. Methods: We used data from the South African National Health Laboratory Service, WC provincial HIV program, and nationwide surveillance data for DCD. We assessed the proportion of eligible patients screened for CrAg (CrAg test done within 30 days of CD4 date) and the prevalence of CrAg positivity. Incidence of DCD among those screened was compared with those not screened. Results: Of 4395 eligible patients, 26.6% (n = 1170) were screened. The proportion of patients screened increased from 15.9% in September 2012 to 36.6% in August 2013. The prevalence of positive serum CrAg was 2.1%. Treatment data were available for 13 of 24 CrAg-positive patients; 9 of 13 were treated with fluconazole. Nine (0.8%) incident cases of DCD occurred among the 1170 patients who were screened for CrAg vs. 49 (1.5%) incident cases among the 3225 patients not screened ( P = 0.07). Conclusions: Relatively few eligible patients were screened under the WC provider-initiated CrAg screening program. Unscreened patients were nearly twice as likely to develop DCD. CrAg screening can reduce the burden of DCD, but needs to be implemented well. To improve screening rates, countries should consider laboratory-based reflexive screening when possible.